Rituals of remembrance: photography and autobiography in postmodern text - Ljungberg, Christina (Aletria: Revista de Estudos de Literatura, 2006)
I argue that the use of photography in postmodern and postcolonial fiction functions firstly, by providing a powerful strategy for drawing attention to the creative and subjective ways in which both verbal and visual images are produced and presented and, secondly, by validating a verbal narrative’s exploration of events as well as supplying a special access to events and experiences that may have been forgotten or unknown. Photography emerges as a unique vehicle for moving between past and present and for thinking photographically as the image of a fleeting moment in time and space is allowed to dissolve into a multitude of possible takes, conflating various viewpoints and space-times of the past, present and future.